Accelerated weathering effects on mechanical, thermal and viscoelastic properties of kenaf/pineapple biocomposite laminates for load bearing structural applications. Issue 2 (31st July 2021) - Kumar, Santosh; Saha, Abir; Bhowmik, Sumit
Abstract: Natural fibers are exceptional renewable resources to develop biocomposite materials for reducing the negative effects on the environment and producing economical and lightweight materials for load bearing semi‐structural applications. The present study is an attempt to develop kenaf/pineapple reinforced bio‐epoxy biocomposite and investigates thermo‐mechanical and viscoelastic properties under accelerated weathering conditions. The compression molding technique is used to develop biocomposite with four different arrangements of kenaf/pineapple laminates. To perform accelerated weathering, laminates are exposed to ultraviolet radiation and humidity conditions with extreme temperature in weathering tester machine. The tensile, flexural, impact, thermogravimetric analysis, thermal conductivity, viscoelastic properties, and water absorption tests are performed before and after accelerated weathering. The results revealed that the hybridization of kenaf/pineapple laminates showed better interfacial strength and stiffness while reducing the moisture sensitivity under accelerated weathering conditions. The morphology and fracture behavior of biocomposites are examined with scanning electron microscopy. Abstract : Natural fibers are exceptional renewable resources for develop bio composite materials. This study provide the effect of accelerated weathering effects on the developed bio composite. Which can act as bench mark to understand sustainability of developed bio‐composite.